2007
DOI: 10.1007/s11244-007-0320-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the oxidative dehydrogenation of ethane over Li/Dy/Mg/O/(Cl) mixed oxide catalysts

Abstract: The microkinetic reaction network of the oxidative dehydrogenation of ethane to ethene over Li/Dy/Mg/O and Li/Dy/Mg/O/Cl catalysts was investigated. With Li/Dy/Mg/O catalysts, the reaction kinetics is compatible with a heterogeneous-homogeneous radical based reaction mechanism. The formation of ethyl radicals on the surface is concluded to be the rate-determining step. In contrast, the reaction kinetics for Li/Dy/Mg/O/Cl is in line with a purely surface catalyzed reaction mechanism. However, also in this case,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…The formation of hypochlorites according to Eq. 1 appears most likely [12], as chloride ions seem to be essential for a high catalytic activity [25].…”
Section: Dependence Of Catalytic Activity and Selectivity On Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of hypochlorites according to Eq. 1 appears most likely [12], as chloride ions seem to be essential for a high catalytic activity [25].…”
Section: Dependence Of Catalytic Activity and Selectivity On Catalystmentioning
confidence: 99%
“…In contrast, halogen promoted alkali and rare earth mixed oxides supported on MgO, SiO 2, and ZrO 2 show high yields of olefins during oxidative conversion of lower alkanes [6][7][8][9][10][11]. In particular, Li-promoted magnesia is a potential catalysts for ODH and cracking of lower alkanes and light petroleum gases (LPG), due to its high selectivity towards olefin formation [6,[10][11][12][13]. Recently, it was demonstrated that alkali metal chlorides supported on SiO 2 or ZrO 2 have also shown excellent catalytic performance in ODH of ethane, although catalyst stability was not satisfactory [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47,48] Thus, the couple CaO-CaCO 3 can be applied in the temperature range of 600-900 8C. [237][238][239][240][241] Moreover, Mg/Al, [242] Li/Dy/Mg, [243,244] and other mixed oxides are capable of reversibly adsorbing CO 2 . Other inorganic adsorbents for CO 2 are MnO 2 , Fe 2 O 3 , calcium hydroxyapatite, hydrotalcite, and zeolite (Na-ZSM-5).…”
Section: Methods For the Reversible Ad-and Absorption Of Carbon Dioxidementioning
confidence: 99%
“…The oxidative dehydrogenation of ethane (ODHE) has been extensively considered as an attractive route for ethylene production compared with traditional steam cracking and catalytic dehydrogenation over the past few decades [1][2][3][4][5][6][7][8][9][10][11]. The metal oxides and metal mixed oxides have been investigated as the promising ODHE catalysts since 1970s due to their great benefits of high theoretical ethane conversion, low energy consumption and low risk of catalyst deactivation caused by carbon deposition [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%